Entrepreneurship in Tourism and Financing through the Regional Operational Programme - Mihaela Ana Pădurean; Ana-Maria Nica; Puiu Nistoreanu (Amfiteatru Economic Journal, 2015)
The European Structural Funds have stood, as early as their very establishment back 1957, for a tool of economic and social harmonization of the Member States of the European Union. The comprehensive process of restructuring and reorganizing the process have led, in time, to emergence of new priority axis and key areas of intervention adapted to the real needs of the single European market. Whether aimed at developing the human resources, improving or creating the specific infrastructure or at fostering entrepreneurship, the Structural Funds have always pursued plugging in the development gaps at both regional and national level. In the depicted background, tourism appears as one of the priority areas for allocation of the European funding. Moreover, fostering entrepreneurship in tourism by allocating Structural Funds entails not only putting in place circumstances fostering establishment of new business entities, but also supporting any initiative which intends to enhance innovation and competitiveness of the existing companies. Further to the investigation of the current progress of the research in the industry, which relied on studies of both foreign and Romanian researchers, a niche has been articulated and become the topic of concern for this article. Thus, the main objective of the article is to determine the immediate effects of accessing the funds available under the Regional Operational Programme (ROP) for the tourism business environment, as a catalyst for entrepreneurship in the respective industry. Subsequent to researching the current economic context of tourism in terms of the specific indicators, a closer look was taken into the use of the Structural Funds under the ROP throughout the recently ended reporting period: 2007- 2013. The data produced was correlated with the SPSS econometrics software. The key outputs include the degree and intensity of the influence of these financial instruments on the tourism business environment, in the shape of future trends, and are listed in the closing section of this article.
Keywords: L26; L83; O19; 330; entrepreneurship; tourism; structural funds; Regional Operational Programme